A colaboração crítica nas aulas de inglês: dessilenciamento, visibilidade e resistência - Francatto, Amanda Maria Enei (2023)
The main goal of this dissertation is to analyze a teaching proposal for an elective English course to understand its contributions to the development of criticalcollaborative students; the organization created for the use of English in the reformulation of decapsulated curricula, and to the transformation of the school context in which the participants were part of. Therefore, I seek to (i) Critically understand the movement triggered by the contradictions that emerge from discussions in the classroom; (ii) Discuss and analyze how (and if) the students' nonsilence and visibility movement occurred; (iii) Evaluate how the ESL classroom was reorganized to create resistance movements. Situated in the field of Critical and Decolonial Applied Linguistics (PENNYCOOK and MAKONI, 2020; MAGALHAES et al., 2021) this study also relies on discussions by Vygotsky (1930, 1934), Freire (1967, 1974) and current researchers who focus on the organization of a criticalcollaborative collective, by using school contexts as social and political spaces for transformational activism. With an epistemological and theoretical-methodological basis in Critical Collaborative Research (MAGALHÃES, 2011, 2016, 2019) and according to Decolonial Pedagogies (WALSH, 2019; MIGNOLO, 2018; SANTOS, 2016), this investigation intended to problematize the transmissive educational organization, which reproduces social relations to meet the market's demands and strengthens the hierarchical power relations reproductions. Organized by a set of resources to promote new forms of engagement through discussions, projects, games/performances, group work, and the use of multiple technologies, this study sought to provide opportunities for teaching and learning English as a enabler of the development of critical and transformational agency in the individuals; and as a way to rethink education and the curriculum in this area as being possible instruments for transforming oppressive and unjust conditions at schools. In this sense, this study aimed to answer the following: 1) What was the movement triggered by the contradictions that emerged from the classroom discussions? 2a) How do the students' nonsilence and visibility movement occur? 2b) How was the ESL classroom reorganized to create resistance movements? This research was carried out in a private school in the state of Sao Paulo and had 12th-grade students as participants. Data production took place throughout the 2021 school year, and all classes were video-recorded. The results indicated the development of new forms of argumentative participation by students both in terms of their agency development and the decapsulation of English classes. In addition, the roles of teacher and students were (re)organized in the classroom. Finally, the research enabled the teacher-researcher to critically reflect on the contradictions identified in her context, which limited her pedagogical work, as well as revealed the decolonial praxis through the lived experiences of individuals who used the English language as a way to promote nonsilence and visibility at school